The Dark Side of High-Fliers: The Dark Triad, High-Flier Traits, Engagement, and Subjective Success - Furnham, Adrian; Treglown, Luke (Frontiers in Psychology, 2021)
The aim of this study was to understand the relationship between bright-side, High Potential and dark-side Dark Triad traits, as well as work engagement on judgements of perceived success. In all, 290 working adults completed questionnaires assessing their High Potential Personality Traits (HPTI), their dark-triad traits, job engagement and self-rated success at work. The data showed that the three dark-triad traits (Narcissism, Psychopathy, Machiavellianism) were systematically and significantly correlated with High Potential traits Adjustment/neuroticism, Tolerance of Ambiguity and Conscientiousness. Three HPTI traits, namely curiosity, Conscientiousness, and courage, were systematically positively correlated with all three engagement measures. Narcissism was strongly related to all measures of engagement. Those with higher scores Adjustment, Courage, and Narcissism and of the male sex, rated their success highest. Job engagement mediated between high-flier and dark-side traits and success ratings. Implications and limitations are discussed.